VD_FINDINFO HC / 2017 / 653 vom 2. August 2017 - VD Tribunal cantonal (2017)
HYPOTHÈQUE LÉGALE, PROPRIÉTÉ PAR ÉTAGES, FRAIS ET CHARGES COMMUNS | 712i CC, 961 al. 3 CC, 249 let. d ch. 5 CPC (CH), 308 al. 1 let. b CPC (CH)